EFFECT OF PERCEIVED ADVANCEMENT OPPORTUNITY TOWARDS TURNOVER INTENTION AMONG ENGINEERS IN MANUFACTURING INDUSTRY - Hanisah Nabihah, Azlan (Universiti Malaysia Sarawak (UNIMAS), 2021)
Turnover intention among employees is a never-ending issue in every organization. Therefore, many research studies have been conducted to identify the factors of turnover intention among the employees. Some research studies reveal a significant relationship between factors such as work-life balance, organizational commitment, job stress and salary, and turnover intention. In the present study, the effect of perceived advancement opportunity towards turnover intention among engineers in Johor manufacturing industry was investigated. The purpose of the study is to identify the direct and indirect effect of perceived advancement opportunity towards turnover intention with the presence of job satisfaction as a mediator. Quantitative research design was applied in the study and the data were collected through a questionnaire that was distributed online to the target population. A total of 120 respondents was gained out of size sample (n= 375) and the response rate is 32%. The data of the present study were analyzed in Statistical Package for the Social Sciences (SPSS). Linear regression and Sobel Test were applied to test the hypotheses and descriptive analysis was applied to describe the scores given by the respondents. The present study reveals that there is a significant indirect effect between perceived advancement opportunity and turnover intention among engineers in manufacturing industry, when perceived advancement opportunity comes across job satisfaction to the turnover intention. Hence, there is a significant mediation effect of job satisfaction towards the relationship between perceived advancement opportunity and turnover intention. The findings of the present study may contribute in existing body of knowledge about turnover intention among engineers in Malaysia manufacturing industry